Increasing the Economic Competitiveness of MSMEs in Nusa Tenggara Barat Through the Utilization of Intellectual Property Rights (IPR) - Siti Yulianah M. Yusuf; Vidya Yanti Utami; Johan Mashuri (Universitas Pamulang, 2023)
Utilization of IPR for MSMEs plays an important role in increasing the economic competitiveness of a business, both individual and legal MSMEs. The problem faced by SMEs is competition in the market. The aim of the research is to determine the increase in the economic competitiveness of Micro, Small and Medium Enterprises (MSMEs in NTB) through the use of Intellectual Property Rights (IPR). This research method is descriptive qualitative. The results of the study show that there are many benefits that can be felt if MSME actors register their IPR products, such as legal protection for these businesses so that other parties cannot use them without the permission of the right owner, because this can hinder the development of MSMEs due to piracy and at the same time act as a stimulus for creativity. society, and increase productivity, the quality and competitiveness of products produced by SMEs in NTB. In addition, the existence of IPR such as product patents will have an effect on increasing the selling price of products because it increases the selling value of products so that they can increase competitiveness in the market.